The 13th IEEE International Symposium on Personal, Indoor and Mobile Radio Communications
DOI: 10.1109/pimrc.2002.1046707
|View full text |Cite
|
Sign up to set email alerts
|

Spatial correlation in indoor MIMO channels

Abstract: This paper presents the analysis of spatial correlation in MIMO channels, calculated from data measured in office environments at 5.2GHz. Results are compared with those from channels generated using a stochastic MIMO channel model and the effect of different comparison metrics is shown. The suitability of the stochastic model under different propagation conditions is also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 7 publications
(10 reference statements)
1
30
0
2
Order By: Relevance
“…These are common performance measures used to validate the performance of a channel model based on measured data. In addition, there is another less common performance measure specific for the Kronecker structure that was used in [3] and [6]. The model error that measures how good the full channel correlation matrix can be modeled as the Kronecker product of the two ends correlation matrices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are common performance measures used to validate the performance of a channel model based on measured data. In addition, there is another less common performance measure specific for the Kronecker structure that was used in [3] and [6]. The model error that measures how good the full channel correlation matrix can be modeled as the Kronecker product of the two ends correlation matrices.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been widely noticed that this channel model has shown different performances under different propagation scenarios. While in [2,3] it is shown that the Kronecker model is very suitable for matching results from measured data with small number of transmit and receive antenna elements, in other studies [5,6] significant differences between the results from the measured data and the predicted results are reported when large number of transmit and receive antennas is used. Although, the simplicity of the Kronecker model makes it an attractive starting point in the analysis of any space-time processing technique.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement campaigns have shown that the Kronecker product correlation model is accurate in capturing the underlying channel statistics under certain conditions [10], but in general, the model underestimates the measured channel capacity [8] and other system parameters.…”
Section: Channel Modelsmentioning
confidence: 99%
“…Multiple-input multiple-output (MIMO) techniques stand as a strong candidate to allow robustness against channel fading and interference as well as to enable high data rates [1,2]. However, the performance of future MIMO wireless communication systems strongly depends on the propagation environment and the antenna array configuration [3] [4]. Previous research results have focused largely on evaluating MIMO system performance under the assumption of uniform linear array (ULA) geometry at both ends with a specific array orientation.…”
Section: Introductionmentioning
confidence: 99%